Standards‐based metadata management for molecular simulations. (4th September 2013) - Grunzke, Richard; Breuers, Sebastian; Gesing, Sandra; Herres‐Pawlis, Sonja; Kruse, Martin; Blunk, Dirk; de la Garza, Luis; Packschies, Lars; Schäfer, Patrick; Schärfe, Charlotta; Schlemmer, Tobias; Steinke, Thomas; et al.
SUMMARY State‐of‐the‐art research in a variety of natural sciences depends heavily on methods of computational chemistry, for example, the calculation of the properties of materials, proteins, catalysts, and drugs. Applications providing such methods require a lot of expertise to handle their complexity and the usage of high‐performance computing. The MoSGrid (molecular simulation grid) infrastructure relieves this burden from scientists by providing a science gateway, which eases access to and usage of computational chemistry applications. One of its cornerstones is the molecular simulations markup language (MSML), an extension of the chemical markup language. MSML abstracts all chemical as well as computational aspects of simulations. An application and its results can be described with common semantics. Using such application, independent descriptions users can easily switch between different applications or compare them. This paper introduces MSML, its integration into a science gateway, and its usage for molecular dynamics, quantum chemistry, and protein docking. Copyright © 2013 John Wiley & Sons, Ltd.